PENGARUH PENEMPATAN PEGAWAI TERHADAP KINERJA PEGAWAI KANTOR CAMAT PAMPANGAN OGAN KOMERING ILIR - Henson Enjein Manurung (Ekonomika, 2021)
The aims of this research are: Identifying the Employee Placement System at the Pampangan Ogan Komering Ilir (OKI) Sub-District Office.,. Identifying Employee Performance at the Pampangan District Office of Ogan Komering Ilir (OKI)., Analyzing the influence of employee placement factors, namely Competence, Qualifications and Motivation on employee performance at the Pampangan Ogan Komering Ilir (OKI) Sub-District Office. and Recommend alternative solutions to improve employee performance at the Pampangan District Office of Ogan Komering Ilir (OKI).The results of the regression analysis show that competence, qualifications, and motivation have a real and positive effect, meaning that the Pampangan District Office of Ogan Komering Ilir (OKI). If you want to improve employee performance, then competence, qualifications and motivation must also be improved. As an implication to the managerial aspect, there is a need for a competency standard in the placement of employees, there is a need for appropriate technical and functional education and training related to the main duties of each employee.